2009
DOI: 10.1007/s12011-009-8339-4
|View full text |Cite
|
Sign up to set email alerts
|

Iron Dialyzability from Hospital Duplicate Meals: Daily Intake

Abstract: Both total and dialyzable iron levels and corresponding dialyzability were determined in 108 duplicate meals during 36 consecutive days. Total mean iron fraction of 5.90 +/- 4.97 mg was found in the meals. The iron supplied by the meals is directly and significantly (p < 0.05) correlated with macromicronutrient content (carbohydrates, fiber, and protein). The mean iron dialyzability (4.81 +/- 3.25%) was low and not significantly different among the three primary meals (breakfast, lunch, and dinner). Significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
4
3
0
Order By: Relevance
“…Positive correlations were observed between total Fe levels and carbohydrate, protein, different amino acids, P, Se, I, K, vitamin E and nicotinic acid content. In agreement with Velasco-Reynold et al ( 18 ) , the present results show that the total Fe supplied in meals is directly related to its macronutrient content.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Positive correlations were observed between total Fe levels and carbohydrate, protein, different amino acids, P, Se, I, K, vitamin E and nicotinic acid content. In agreement with Velasco-Reynold et al ( 18 ) , the present results show that the total Fe supplied in meals is directly related to its macronutrient content.…”
Section: Resultssupporting
confidence: 93%
“…Fe content in the analysed daily duplicate meals ranged from 9·50 to 40·00 mg, with a mean of 18·50 mg (Table 3). These values are similar to those reported by Velasco-Reynold et al ( 18 ) for duplicate meals provided daily in hospitals in Granada, Spain (17·7 mg; range 9·51–42·00 mg). Our mean value of 18·50 mg/d is higher than the estimated average requirement of 8·1 mg/d proposed by the US Institute of Medicine ( 2 ) and is similar to the Fe intake estimated in other Spanish epidemiological studies, as reported by Fernández-Morales et al ( 19 ) in female adolescents (16·63–17·21 mg/d), although higher than that reported by the enKid study in women aged 18–24 years (12·9 mg/d) ( 8 ) .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…On the other hand, other researchers reported that the Mg dialysabilities decreased slightly with increasing phytic acid contents [5,33]. Dialysable Mg 0.378 ** Potassium 0.374 *** Ca dialysability 0.331 *** Dialysable Zn b 0.296 *** Ascorbic acid 0.380 *** Cr dialysability c 0.463 * * p≤0.001; ** p<0.01; *** p<0.05 a Total and dialysable Cu determined in duplicate meals by GFAAS [30] b Total and dialysable Zn determined in duplicate meals by GFAAS [40] c Total and dialysable Cr determined in duplicate meals by GFAAS [31] d Total and dialysable Fe determined in duplicate meals by FAAS [41] Vitamin A and K contents of meals estimated by the food consumption tables compiled in the statistics programme Dietsource 2.0 also enhanced significantly with the Mg dialysability levels found (Table 4). …”
Section: Total and Dialysable Mg Fractions And Corresponding Element mentioning
confidence: 99%